Historiographic Researches to the Process of Illiteracy Liquidation (1920-1930-s) - Olha Boiko (Pedagogical Discourse, 2013)
Historiographic analysis of the process of illiteracy liquidation on the territory of Ukraine in 1920-1930-s has been done in the article, three periods of historiographic researches have been selected. The author carries out the analysis of scientific works, devoted to the research of this problem. Special attention is concentrated on the research of printing works of the scientisits of the past and the works of the  modern research workers fas for the study of the process of illiteracy liquidation on the territory of Ukraine in 1920-1930-s. The history of illiteracy liquidation as the integral phenomenon from the point of view of historiography has been offered in the article. Systematization, classification and generalization of the accumulated knowledge, has been conducted through the historiographic analysis of the proper sources.